Insulin resistance in drug naive patients with multiple sclerosis - Kostić, Smiljana; Kolić, Ivana; Raičević, Ranko; Stojanović, Zvezdana; Kostić, Dejan; Dinčić, Evica (Vojnosanitetski pregled, 2017)
Background/Aim. Due to the fact that there is a relatively small number of data related to systemic insulin abnormalities in the multiple sclerosis (MS), the main objective of our study was to determine whether a dysbalance of glucose and insulin metabolism exist in patients with natural course of MS. Our hypothesis was that the metabolic disorder that characterizes state of the insulin resistance (IR) and reduced insulin sensitivity (IS) in untreated patients with MS could play a role in disease progression and degree of functional disability. Methods. The study included 31 patients with relapsing-remitting (RR) MS and 14 healthy controls from the same geographic area matched by age, ethnicity and number of smokers. The glucose tolerance, IS, and IR were examined using an oral glucose tolerance test (OGTT) and using basal plasma glucose and insulin levels. The functional disability and disease progression were evaluated by the Expanded Disability Status Scale (EDSS) and Multiple Sclerosis Severity Score (MSSS). Results. The MS patients tolerated glucose equally well as the healthy controls. Basal concentrations of insulin were significantly higher in the MS group (p
Keywords: multiple sclerosis; insulin resistance; glucose tolerance test; surveys and questionnaires